2018
DOI: 10.1111/1467-8500.12318
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Level Policy Implementation: A Case Study on China's Administrative Approval Intermediaries’ Reforms

Abstract: Policy output and outcome shortfalls are often attributable to deficits in implementation. Drawing on data collected from multi-level governmental documents and in-depth interviews regarding the ongoing reforms of the use of 'administrative approval intermediaries' in China, we identified a genre of policy implementation in which the policy implementers themselves are targets of reform. These implementers swing between fulfilling tasks and deviation from formal requirements. By illustrating how the implementat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In China, for instance, the share of the state sector in the value of industrial output, while dropping precipitously from 78 percent in 1978, has stabilized at a high level of 22 percent in 2014. 5…”
mentioning
confidence: 99%
“…In China, for instance, the share of the state sector in the value of industrial output, while dropping precipitously from 78 percent in 1978, has stabilized at a high level of 22 percent in 2014. 5…”
mentioning
confidence: 99%
“…Previous research on China's ALCs has found that the diffusion of ALCs in China is influenced by local socioeconomic conditions, official characteristics, and external pressures (Zhu and Zhang 2016;Zhu and Zhao 2018). More qualitative information on the creation of ALCs in China can be found in Zhu and Jiao (2012), Zhu (2014), and Zhang and Rosenbloom (2018).…”
Section: Methodsmentioning
confidence: 99%
“…As Zhan et al (2013) argued, implementation deficits in China have been an enduring problem. This administrative structure leaves subcentral government with significant discretion on how to achieve the central-level policy goals thereby exacerbating the complexity of policy implementation (N. Zhang & Rosenbloom, 2018).…”
Section: Policy Implementation Structure and Deficits In Chinamentioning
confidence: 99%
“…Policy deficits are usually considered as a flaw in policy goal fulfillment (Ahlers & Schubert, 2014;Sabatier & Mazmanian, 1979). Policies can be eroded to a great extent in the process of multilevel implementation (N. Zhang & Rosenbloom, 2018). The probability of implementation deficits increases as the number of administrative layers increases (Elmore, 1979).…”
Section: Middle-level Implementation Deficitsmentioning
confidence: 99%
See 1 more Smart Citation